iPhone JavaScript Cookbook - Montoro, Arturo Fernandez (Packt Publishing, 2011)
Written in a cookbook style, this book offers solutions using a recipe-based approach. Each recipe contains step-by-step instructions followed by an analysis of what was done in each task and other useful information. The cookbook approach means you can dive into whatever recipes you want in no particular order. This book is for web developers interested in applying their knowledge for building web applications for iOS devices. You can develop your own iPhone web applications using nothing but JavaScript combined with XHTML and CSS. You can even give these apps a native look and feel though you won't be able to submit them to the App Store. You will develop an application for iOS without having to learn the Objective-C programming language. This is the book for any iPhone developer looking to side-step Apple's totalitarian App Store regime.